The complete chloroplast genome sequence of the Citrullus lanatus L. Subsp. Vulgaris (Cucurbitaceae). Issue 1 (1st January 2016) - Zhu, Qianglong; Cui, Haonan; Zhao, Yulong; Gao, Peng; Liu, Shi; Wang, Pengfei; Luan, Feishi
Abstract: Watermelon is one of the worldwide popular summer fruits and well-known for colourful, sweet, and juicy flesh. The complete nucleotide sequence of cultivated watermelon ( Citrullus lanatus L. subsp. vulgaris) chloroplast genome has been determined in this study. The genome was composed of 156, 906 bp containing a pair of inverted repeats (IRs) of 26, 082 bp, which was separated by a large single-copy region of 70, 063 bp and a small single-copy region of 17, 895 bp. A total of 114 genes were predicted included 80 protein-coding genes, four rRNA genes, and 30 tRNA genes. Phylogenetic analysis revealed that C. lanatus and other three species belonging to the genus Cucumis were closely clustered into a clade, the family Cucurbitaceae.